New connectivity in the Bay of Bengal : opportunities and perspectives of the Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) - Wagner, Christian; Tripathi, Siddharth (2018)
Zusammenfassung: Owing to the increased commitment from India, the Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) has experienced a revival since 2016. Firstly, India is hoping to be able to develop better the country’s hard-to-reach northeast by intensifying regional cooperation. Secondly, given the Chinese Belt and Road Initiative (BRI) investments in neighbouring countries, it aims to reinforce its claim to leadership in the region. From an international perspective, BIMSTEC is an essential building block in India’s Act East policy in the context of the renewed importance of the Indo-Pacific region. With the support of BIMSTEC, Germany and the European Union (EU) can deepen their strategic partnership with India whilst simultaneously increasing their visibility in the Bay of Bengal..